Analisis Hujan Ekstrim Probable Maximum Precipitation (PMP) menggunakan metode Hersfield dan Perhitungan Debit Banjir: (Studi Kasus: Sungai Kluet Utara Kabupaten Aceh Selatan) - Akmal, Akmal; Yulia, Yulia; Aranda, Aris (Tameh, 2022)
Extreme rain is rain with the lowest intensity of 50 mm/24 hours or 20 mm/hour. River is an elongated surface water flow and flows from a higher place (upstream) to a lower place (downstream). The area of KIuet is 1429.93 km and the area of Kluet River is 163.51 km2 and the length of the river is 68.26 km. The problem is that Kluet Utara River experiences high rainfall, resulting in overflows that flatten agricultural land and submerge residential areas. The purpose of the study was to calculate the planned return period rainfall, analyze the PMP (probable Maximum Precipitation) value and analyze the flood discharge to evaluate the PMF (Probable Maximum Flood) value and the return flood discharge. The benefits of this research are used to see the PMF value and return period rainfall to analyze the frequency of flooding KIuet Utara Watershed (DAS). The scope of the research was to calculate rainfall and flood discharge in KIuet Utara Watershed and secondary data which includes 10 years rainfall data obtained from BMKG (Meteorology, Climatology and Geophysics Agency) Indrapuri Aceh Besar and watershed maps obtained from PT. Mediatama Indoconsult. Processing of rainfall data on return period used Log Pearson III Method and PMP used Hersfield Method while calculating the planned flood discharge using Melchior Method. The results of the research is the rainfall value for the return period for the lowest rainfall in the 2 year return period is as high as 211,836 mm and the highest rainfall for the 1000 year return period is 566,239 mm, so that the flood discharge plan for the return period for the lowest flood discharge in the 2 year return period is equal to 2061,342 m3/s and the highest flood discharge at the 1000 year return period is 5510,490 m3/s. The PMP value was obtained at 2128,432 mm so that the PMF was obtained at 20714,772 m3/s. Log Pearson III and PMP methods can be used to calculate the rainfall in KIuet Utara and the results from the rainfall are used to calculate the planned flood discharge using Melchior Method.